1982
DOI: 10.1007/bf02553603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between oral and systemic antibiotics and their combined use for the prevention of complications in colorectal surgery

Abstract: Ninety patients were included in this prospective randomized trial. Each required electric colorectal surgery and was prepared for operation with oral preoperative antibiotic therapy, systemic peroperative therapy, or by a combination of both. The number of each type of septic postoperative complication and their total did not differ between the group treated by oral antibiotics prior to operation and the group treated peroperatively with systemic antibiotic therapy. The total number of septic complications (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…2). The 16 studies included in the meta-analysis are outlined in Table 1 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. No eligible trial was found prior to 1980, and the first trial included in the SWI meta-analysis was from 1982.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The 16 studies included in the meta-analysis are outlined in Table 1 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. No eligible trial was found prior to 1980, and the first trial included in the SWI meta-analysis was from 1982.…”
Section: Resultsmentioning
confidence: 99%
“…Of the antibiotic regimens used in the intravenous antibiotic only arms, only 2 studies utilized a regimen that is not currently recommended by the Surgical Care Improvement Project (SCIP) guidelines [20,21,29]. In 3 other studies (2 of which included in the SWI meta-analysis), the intravenous antibiotics regimen had reduced gram-negative coverage [13,14,16]. In 6 of the 16 studies the intravenous antibiotics used in combination with oral antibiotics were not the same ones used in the intravenous antibiotic only arm (Table 1).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The issue of the best route of perioperative antibiotic prophylaxis is still controversial, because both parenteral and oral antibiotic prophylaxis is effective in colon surgery [15][16][17][18]. Most studies evaluated the effect of adjunctive parenteral antibiotics after oral antibiotic prophylaxis, or compared the effect of the two routes of administration [8,15,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the two methods together yielded a 5% rate of surgical site infection whereas the patients who received only systemic antibiotics and no oral antibiotic bowel preparation had a 16% rate of surgical site infection. In this same publication, Lewis identified 12 additional studies where systemic antibiotics were compared to systemic plus oral antibiotics in colon surgery (Table 2) [24][25][26][27][28][29][30][31][32][33][34][35]. The meta-analysis demonstrated marked statistical significance (p 辖 0.0001) in favor of lower surgical site infections with combinations of the two methods.…”
Section: Systemic Versus Oral Antibiotics In Colon Surgerymentioning
confidence: 95%